Discourse Moves and Emotion in Knowledge Building Discourse and Metadiscourse - Gaoxia Zhu; Marlene Scardamalia; Matthew Moreno; Michael Martins; Raadiyah Nazeem; Zhixin Lai (Frontiers in Education, 2022)
This paper explores the possibility that knowledge building metadiscourse-discourse about knowledge building-can produce a positive feedback loop, with positive emotional state and knowledge advancement serving to increase each other. Grades 2 and 3 students’ utterances over several months were analyzed as a unit of study, starting with identification of each discourse move and corresponding emotion, defined as a state. These states were then analyzed over time, with a focus on metadiscourse sessions in which students reflected on earlier discourse to identify questions and ideas to be pursued in greater depth. Each discourse move-emotional state was analyzed to determine frequency, transition from one state to another, and spread of each state such as “reflection and positive” and “proposing new directions for inquiry and curiosity.” These two states were among the most frequently occurring in the metadiscourse sessions and virtually absent in other discourse sessions. Transition rates indicated that reflection tended to trigger more reflection, and proposing a new direction led to more proposals for new directions. Sequential pattern analysis suggested sub-sequences specific to metadiscourse sessions. Overall, results indicate that engaging in metadiscourse contributes to students’ productive KB and positive emotions.